Graphene: excursus of the evolution of processes and products - M. Covelli; A. Cusanno; E. Aiello; A. Greco Lucchina; A. Mastroianni; F.M. Ceruso; G. Palumbo (Publymed, 2022)
OBJECTIVE: Graphene and derived materials are a new class of fundamental nanomaterials. Thanks to the unique characteristics as excellent electrical conductivity, biocompatibility and thermal properties, this material has aroused a considerable interest in the scientific community from its discovery. The purpose of this work is to pursue the various steps chronologically that led from discovery to single production and in series of graphene, focusing on the advantages and disadvantages of the techniques going to underline the validity and importance of each, on the basis of the searches to be carried out and the products finished to be obtained. In the second section of this work, however, we focused on the evolution of the applications of this super material over time. In fact, graphene and bidimensional materials in graphene have been significantly used in various areas of biomedical research such as fabric engineering, regenerative medicine, bioimaging with application in neural engineering and in the clinic, with different future perspectives still to be completed.